Relationship between Emotional Intelligence, Self-Esteem, Anxiety and Academic Stress of the Gifted Children in Oyo State, Nigeria (Global Journal of Human-Social Science, 2016)
This study investigated the relationship between emotional intelligence, self-esteem, anxiety and academic stress of gifted children in Oyo State, Nigeria. Descriptive research design of ex-post-facto was used in the study. One hundred and twenty (120) gifted children were selected from public secondary schools in Oyo State, Nigeria. The respondents were measured with five standardized scales including; (i) Self -esteem Scale (ii) Student Academic Stress Scale,(iii) Emotional intelligence Scale, (iv) Giftedness Scale and (v) State and Trait Anxiety Inventory. Three research Questions were raised and answered in the study. The data obtained were analyzed using Pearson's Product Moment Correlation (PPMC) and Multiple Regression analysis. The result showed that there was significant relationship among all the independent variables (emotional intelligence, self-esteem and anxiety) and academic stress. There was joint contribution of emotional intelligence, self-esteem and anxiety on academic stress among gifted students in Oyo state. Also there was relative contribution of emotional intelligence, self-esteem and anxiety on academic stress among gifted students in Oyo state.
Keywords: emotional intelligence; selfesteem; anxiety; academic stress